Hematuria as an Early Sign of Multisystem Inflammatory Syndrome in Children: A Case Report of a Boy With Multiple Comorbidities and Review of Literature - Generalić, Ana; Davidović, Maša; Kos, Ivanka; Vrljičak, Kristina; Lamot, Lovro (Frontiers in Pediatrics, 2021)
Introduction: While clinical course of SARS-CoV-2 infection seems to be milder or asymptomatic within pediatric population, growing attention has been laid to the rare complication elicited by virus, multisystem inflammatory syndrome in children temporarily associated with COVID-19 (MIS-C). Published definition and criteria of MIS-C include persistent fever, multisystem involvement and elevated markers of inflammation, without obvious microbial inflammation or other plausible diagnosis. However, the aim of this case report is to emphasize diversity of symptoms of MIS-C, beyond the defined criteria. Case presentation: We present a ten-year-old boy with 8p23.1 microdeletion syndrome and multiple comorbidities who initially came to our attention due to hematuria, persistent fever, rash and elevated markers of inflammation. Within the next two days, his condition worsen despite the broad-spectrum antibiotic therapy. Assuming his past history of SARS-CoV-2 exposure, MIS-C was suspected. High level of clinical suspicion was further supported by significant clinical features (vomiting, abdominal pain, conjunctivitis, arrhythmia and mild left ventricular systolic dysfunction with pleural effusion) along with laboratory findings (elevated ESR, CRP, proBNP, D-dimers and fibrinogen, positive IgG SARS-CoV-2 antibodies and negative microbiological cultures). The patient was given intravenous immunoglobulin (IVIG) and began to show instantaneous clinical and laboratory improvement. Conclusion: Despite numerous reports of MIS-C cases in children, there are still many uncertainties regarding the clinical presentation and laboratory findings, as well as mechanisms beyond this intriguing disorder. In our case for the first time hematuria is reported as an early symptom of MIS-C, suggesting a possible underlying vasculopathic mechanism. We strongly believe that reporting various manifestations and outcomes in MIS-C patients will lead to improved diagnosis, treatment and overall understanding of this novel inflammatory condition.